Didactical design for online learning in ordering fractions - Isnawan, Muhamad Galang; Alsulami, Naif Mastoor (Universitas Terbuka, 2024)
During COVID-19, various obstacles were experienced during learning, including in learning mathematics. Learning had to be carried out online. Therefore, learning designs were also attempted to be made online. The learning design in this research was prepared using didactical design research. Participants in this research were 29 students at one of the junior high schools in Indonesia. The researcher was the main instrument in this research, along with several additional instruments, such as the fraction sequence test, interview guide, and online learning design. The data were analyzed using thematic analysis and qualitative analysis. The research results revealed that the factor that caused students to experience obstacles in ordering fractions was due to students’ low prerequisite knowledge regarding LCM (conceptual ontogenic obstacle). The online learning design offered then facilitated students to solidify their understanding of LCM before entering the core learning activities. Online learning design was also developed using the theory of didactical situations. After implementation, information was obtained that the learning obstacles experienced by students had no longer reappeared. Therefore, learning in schools should ensure that students have a good understanding of the prerequisites before starting the core learning activities.